2007
DOI: 10.1152/ajpendo.00089.2007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of TNF-α neutralization on adipocytokines and skeletal muscle adiposity in the metabolic syndrome

Abstract: Ahima RS, Grinspoon SK. Effects of TNF-␣ neutralization on adipocytokines and skeletal muscle adiposity in the metabolic syndrome. Am J Physiol Endocrinol Metab 293: E102-E109, 2007. First published March 20, 2007; doi:10.1152/ajpendo.00089.2007.-In a prior study, we have shown that tumor necrosis factor (TNF)-␣ neutralization improves inflammatory markers and total adiponectin in patients with the metabolic syndrome, without improving insulin sensitivity. In this study, we sought to extend our understanding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(62 citation statements)
references
References 64 publications
1
58
0
3
Order By: Relevance
“…Among factors having a role in the differential isoform secretion in respect to the fat depot, the regulatory interaction between adipokines should be mentioned. For instance, tumor necrosis factor-a showing different expression levels in the two fat depots 42,43 directly contributes to the reduction of adiponectin in adipocytes, 44 and tumor necrosis factor-a neutralization increases not only total plasma adiponectin levels 45 but also the ratio of HMW to total adiponectin in obese subjects. 46 This suggests other potential mechanisms in the differential regulation of adiponectin isoforms in fat depots.…”
Section: Discussionmentioning
confidence: 99%
“…Among factors having a role in the differential isoform secretion in respect to the fat depot, the regulatory interaction between adipokines should be mentioned. For instance, tumor necrosis factor-a showing different expression levels in the two fat depots 42,43 directly contributes to the reduction of adiponectin in adipocytes, 44 and tumor necrosis factor-a neutralization increases not only total plasma adiponectin levels 45 but also the ratio of HMW to total adiponectin in obese subjects. 46 This suggests other potential mechanisms in the differential regulation of adiponectin isoforms in fat depots.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the anti-inflammatory drugs are those that are routinely used in the treatment of rheumatoid arthritis, such as TNF-␣ antibodies (Etanercept, Infliximab, Humira, etc.) (62,73,93,114), an IL-1 antibody (XOMA052) or inhibitor (Anakinra) (71), an IL-6 antibody (Tocilizumab) (94,121), and an inflammation suppressor (salsalate, a dimer of salicylic acid) (26,91). The therapeutics reduced inflammation in the patients in all of the clinical trials, as indicated by a decrease in the inflammatory markers C-reactive protein and IL-6.…”
Section: Anti-inflammatory Therapy In Clinical Trialsmentioning
confidence: 99%
“…82 However, the evidence that this work translates to humans is, at present, rather less convincing. Indeed, to date there is little published evidence that the use of non-specific 83 or specific 84 anti-inflammatory agents has any sustained, significant impact on human insulin sensitivity.…”
Section: The Infl Ammatory Hypothesismentioning
confidence: 99%